(untitled) (CIPEEX, 2026)
The Cerrado, recognized as the world’s most biodiverse savanna, faces severe threats from agricultural expansion and habitat fragmentation, which compromise key ecological interactions such as pollination. In this context, this study aimed to investigate the reproductive biology of Justicia nodicaulis (Acanthaceae), a species with a typical trochilophilous syndrome that remains poorly studied in the Goiás Cerrado. Fieldwork was conducted along the Tucano Trail in Anápolis (GO) during August and September 2025, including phenological monitoring, photographic documentation, and observations of floral visitors. A complementary literature review focused on pollination within the genus Justicia. Results indicate that the species exhibits early flowering at the end of the dry season, with tubular corollas adapted to hummingbird pollination, although no visitors were recorded during the observation period. The review confirmed trochilophily as the predominant syndrome in the genus, with pollination by species such as Phaethornis and Amazilia fimbriata, and reports of self-compatibility in some congeners. These findings suggest that J. nodicaulis possesses floral traits consistent with vertebrate pollination, though the absence of visitors may reflect seasonal factors or local anthropogenic pressures. The first documentation of its phenology in Goiás contributes to the understanding of Acanthaceae reproductive biology in the Cerrado and supports future research on reproductive success and responses to environmental change, essential for conservation strategies in the biome.